Suscetibilidade de trichophyton rubrum e trichophyton mentagrophytes frente a agentes antifúngicos - Liscano, Mari Glei Hernandez (2015)
Dermatophytes are a group of fungi with the capacity to invade keratinized tissues and cause infections called dermatophytosis. They are common worldwide, and does not know the true incidence because it is not notifiable. The species Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis, Trichophyton tonsurans, and Epidermophyton floccosum are often reported as the cause of infections in humans. Studies show that immunocompetent patients are affected by dermatophytes in a 40% rate, and that those patients with a weakened immune system, increase the occurrence of these dermatophytes, as well as the severity of the lesions. Entering this context, the present study aimed to evaluate the susceptibility profile of antifungal front of two species most common dermatophytes, T. rubrum and T. mentagrophytes, found in clinical samples from patients treated at HUSM, these cultures were stored-in one mycology collection, which were performed in vitro by broth microdilution technique as per the recommendations of the document M38-A2 of Clinical Laboratory Standarts. The analysis of the antifungal susceptibility profile was made from the species T. rubrum (n = 30) and T. mentagrophytes (n = 30) of the nail lesions, which were the most frequent injuries in previous studies by Lopes, O.J. et al. (1999). The minimum inhibitory concentrations (MICs) were recorded lower front terbinafine (from 0.03 to 0.5 μg / mL) and itraconazole (0.03 to 0.5 μg / mL). Conversely, the higher MICs to fluconazole were forward (1-32 μg / mL) and griseofulvin (0.25 to 4.0 μg / mL). Resistant isolates were detected against fluconazole (15/25%) and griseofulvin (17 / 28.3%). Cross-resistance between azole was not detected, however, the front multidrug resistance to fluconazole and griseofulvin was detected in six isolates [T. rubrum (n = 5) and T. mentagrophytes (n = 1)], representing 10% of the isolates. In general, the susceptibility profile showed high sensitivity to antifungal front, being detected only against fluconazole resistant isolates and griseofulvin in small percentages. Still, multidrug resistance was detected against the fluconazole and griseofulvin in six isolated.